Determination of advantame in fermented milk using Captiva EMR-Lipid combined with UHPLC-MS/MS - HUANG Huimin, YANG Guang, DUAN Hu, LIU Ning, XIE Jiangna (Zhongguo niangzao)
The study established a detection method for determining the content of advantame in fermented milk by combining an enhanced lipid removal purification technology (Captiva EMR-Lipid) with ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The sample was salted out by sodium chloride, ultrasonic extracted by 1% formic acid acetonitrile solution, purified by Captiva EMR-Lipid solid phase extraction column, eluted with methanol -0.1% formic acid aqueous solution as mobile phase gradient, and using external standard method of matrix matching standard curve under the mode of positive ion scanning of heated electrospray ion (HESI) source and selected ion monitoring (SRM). The results shown that the linear relationship of advantame was good within the range of 0.2-500 ng/ml, correlation coefficient R2 was 0.998 3, limit of detection (LOD) was 0.6 μg/kg, limit of quantitation (LOQ) was 2 μg/kg, and the recovery rates were 87.9%-102.5%. The method had the advantages of simple extraction, high sensitivity, and good accuracy, and was suitable for the detection of advantame in fermented milk.